2017
DOI: 10.1177/2058460116687174
|View full text |Cite
|
Sign up to set email alerts
|

The additional utility of apparent diffusion coefficient values of clear-cell renal cell carcinoma for predicting metastasis during clinical staging

Abstract: BackgroundThe apparent diffusion coefficient (ADC) value is known to be an indicator of tumor activity. The ADC value of high-grade clear-cell renal cell carcinoma (RCC) is significantly lower than that of low-grade clear-cell RCC.PurposeTo investigate the utility of ADC values of clear-cell RCC by comparing ADC values between groups with T1a RCC (tumor size ≤ 4 cm) without metastasis and the group with metastasis.Material and MethodsA retrospective review was performed on 51 patients with 51 RCCs who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Our result agreed with the previous study, which found a statistically significant difference in the ADC [25].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our result agreed with the previous study, which found a statistically significant difference in the ADC [25].…”
Section: Discussionsupporting
confidence: 94%
“…Thus, the minimum ADC was observed to be an independent factor for recurrence of RCC after nephrectomy [8]. Yoshida et al exhibited a measurably noteworthy distinction in the ADC between T1a RCC (estimate ≤ 4 cm) with or without lymph nodes or metastasis [9]. Therefore, we hypothesize that the ADC value may be one of the prognostic factors for tumor aggressiveness in patients with RCC.…”
Section: Introductionmentioning
confidence: 69%
“…MRI-derived ADC values are useful in characterizing tumor activity [ 54 ]. Some studies [ 55 , 56 ] that evaluated the utility of ADC to differentiate low- from high-grade ccRCC reported that MRI has a favorable predictive accuracy in detecting high-grade ccRCC (AUC = 0.80).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, two approaches are attractive for researchers at present. One is the Apparent diffusion coefficient (ADC) value in MRI imaging (14), and the other is CT-based semiquantitative and quantitative techniques (15,16).…”
Section: Introductionmentioning
confidence: 99%